SOSIALISASI JAMBAN SEHAT DENGAN KEJADIAN STUNTING DI KELURAHAN WAY GUBAK, KECAMATAN SUKABUMI, KOTA BANDAR LAMPUNG (Socialization of healthy latrines with stunting events in way gubak village, Sukabumi district, Bandar lampung regency) - Natalina, Natalina; Ergantara, Rani Ismiarti; Wulandari, Diah Ayu; Andriani, Rida Yuliana; Munira, Munira; Agustin, Nesti (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2022)
Stunting in infants and children has until now become a major problem in the world, including Indonesia. One of the risk factors for stunting is poor environmental sanitation. Sukabumi Subdistrict has a prevalence of stunting in Bandar Lampung Regency so that it is one of the priorities of the Bandar Lampung Regency Government in an effort to reduce stunting. A healthy latrine is a family sanitation facility that must be owned by every household. The purpose of this activity is to increase public knowledge about healthy latrines by analyzing the relationship between the condition of the latrine and the incidence of stunted children. This research was conducted in the 1st ward of Way Gubak Village, Sukabumi District on 03 August 2022. The method used in this activity is an interactive lecture using a proyector slide tool prop with a presentation on small-scale, household and communal healthy latrines, followed by a question and answer. This activity was attended by 46 people from the way Gubak village.The results obtained include the community being very enthusiastic about the material provided; this can be seen from the questions asked by the community and the number of people who are able to answer questions. With this activity, it is hoped that it can change people's minds that healthy latrines are necessary for children's growth.